2011
DOI: 10.1074/jbc.m110.190678
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Inducible Nitric-oxide Synthase by the SPRY Domain- and SOCS Box-containing Proteins

Abstract: Inducible nitric-oxide synthase (iNOS, NOS2) plays a prominent role in macrophage bactericidal and tumoricidal activities. A relatively large amount of NO produced via iNOS, however, also targets the macrophage itself for apoptotic cell death. To uncover the intrinsic mechanisms of iNOS regulation, we have characterized the SPRY domain-and SOCS box-containing protein 1 (SPSB1), SPSB2, and SPSB4 that interact with the N-terminal region of iNOS in a D-I-N-N-N sequence-dependent manner. Fluorescence microscopy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 42 publications
1
56
0
Order By: Relevance
“…In addition, macrophages from mutant-Nrdp1 (lacking E3 ubiquitin ligase) transgenic mice also showed similar impaired expression of iNOS after LPS stimulation (data not shown), suggesting that Nrdp1 inhibits iNOS expression in an E3 ubiquitin ligase-independent manner. iNOS protein level in cells can be up-regulated by increased transcription of iNOS gene or the decreased ubiquitinationand proteasome-mediated degradation of iNOS protein (22,23). A variety of transcription factors, such as nuclear factor-B (NF-B), activating protein-1 (AP-1), C/EBP, C/EBP␤, octamerbinding transcription factor-1 (Oct-1), have been proved to bind with the iNOS promoter and enhance the transcription of the iNOS gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, macrophages from mutant-Nrdp1 (lacking E3 ubiquitin ligase) transgenic mice also showed similar impaired expression of iNOS after LPS stimulation (data not shown), suggesting that Nrdp1 inhibits iNOS expression in an E3 ubiquitin ligase-independent manner. iNOS protein level in cells can be up-regulated by increased transcription of iNOS gene or the decreased ubiquitinationand proteasome-mediated degradation of iNOS protein (22,23). A variety of transcription factors, such as nuclear factor-B (NF-B), activating protein-1 (AP-1), C/EBP, C/EBP␤, octamerbinding transcription factor-1 (Oct-1), have been proved to bind with the iNOS promoter and enhance the transcription of the iNOS gene.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of signals can regulate Arg1 expression in macrophages. Among them, IL-4 is by far the most potent cytokine that polarizes macrophages to AAM (22). As the Arg1 level was significantly higher in Nrdp1-TG macrophages than that in WT macrophages, we further explored whether Nrdp1 influences the M2 macrophage polarization triggered by IL-4.…”
Section: Nrdp1 Up-regulates Arg1 Expression Inmentioning
confidence: 99%
“…SPSB1, 2 and 4 are similar both in amino acid sequence and in function. We, and others, have recently shown that inducible nitric oxide synthase (iNOS/NOS2) is a physiological target of the mammalian SPSB1 and SPSB2 proteins, suggesting a role for these proteins in regulating the innate immune response (70)(71)(72). SPSB1, 2 and 4 interact via their SPRY domain with a DINNN motif in the N-terminal region of iNOS and through the SOCS box-associated CRL ubiquitinate iNOS causing it to be degraded by the proteasome.…”
Section: Spry Domain Socs Box Proteinsmentioning
confidence: 99%
“…Recently, SPSB1 and SPSB2 have been shown to interact with inducible nitric-oxide synthase (iNos), targeting it for ubiquitination and proteasomal degradation and implicating the SPSB proteins in regulating the host response to infection (37)(38)(39). SPSB1 has also been reported to interact with c-Met to enhance the hepatocyte growth factor-induced Erk-Elk-1-Sre pathway by an unknown mechanism (27), whereas SPSB1, -2, and -4 have been reported to bind to the intracellular protein prostate apoptosis response 4 (Par4) (28).…”
mentioning
confidence: 99%